Illiteracy and social exclusion: Notes from the dialogue with Freire, Arroyo, Marta Oliveira and Antônia: Illiteracy and social exclusion: Notes from the dialogue with Freire, Arroyo, Marta Oliveira and Antônia - Sol Souza, Andréia Luciane (2022)
This text marks the place of literacy as a “social good” unevenly distributed in society, in which the popular classes are disadvantaged (FREIRE, 2008). The present work establishes a “dialogue” between Paulo Freire, Miguel Arroyo, Marta Oliveira and Antônia – black, working and illiterate woman. This text points out the relationship between illiteracy and social exclusion, analyzing the context and life of Antônia, in its connections with youth and adult education and in the implications of theoretical-methodological challenges to deal with this theme. A dialogue between student Antônia, her life trajectory inserted in the broader context of illiteracy and popular education actions. Thus, bring elements that can contribute to the understanding of situations placed to illiterate adults when dealing with occasions that require the use of reading and writing codes. In this sense, we invite readers to reflect on Antônia's story not as an individual story, but as a collective story, which presents the reality of many non-literate adults.